Electromagnetic radiation, scattering, and diffraction - Pathak, P. H. 1942-; Burkholder, R. J. (John Wiley & Sons, Inc., 2022)
"This book is designed to provide an understanding of the behavior of EM fields in radiation, scattering and guided wave environments, from first principles and from low to high frequencies. Physical interpretations of the EM wave phenomena are stressed along with their underlying mathematics. Fundamental principles are stressed, and numerous examples are included to illustrate concepts. This book can facilitate students with a somewhat limited undergraduate EM background to rapidly and systematically advance their understanding of EM wave theory that is useful and important for doing graduate level research on wave EM problems. This book can therefore also be useful for gaining a better understanding of problems they are trying to simulate with commercial EM software and how to better interpret their results. The book can also be used for self-study as a refresher for EM industry professionals"- Resumé vydavatel
Keywords: elektromagnetické vlny; rozptyl (fyzika); difrakce; electromagnetic waves; scattering (physics); diffraction; elektronické knihy; učebnice; electronic books; textbooks